1988
DOI: 10.1515/polyeng.1988.8.1-2.19
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the State of Cure in Vulcanizates After Removal From the Mold

Abstract: The progress of cure reactions was observed for rubber sheets during the cooling period after their extraction from the mold. The study was performed by considering either motionless air at 125°C and water at 12°C for cooling the rubber previously cured in a mold kept at 160eC. A significant increase in the state of cure was calculated with the help of a numerical model for the vulcanizates, especially in the case of air at 125°C. An improvement in physical properties such as the swellling in toluene, and mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…The heat conduction equation and the initial and boundary conditions are given in equations (1)- (5).…”
Section: Model and Solution Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The heat conduction equation and the initial and boundary conditions are given in equations (1)- (5).…”
Section: Model and Solution Methodsmentioning
confidence: 99%
“…For some components, the cure accumulated during the cooling phase can be a significant fraction of the overall cure at some locations within the component. 5 The convection cooling and the resulting state of cure distribution of a onedimensional (1D) rectangular component that has been ejected from a mold after attaining a specified minimum state of cure has been successfully modeled and validated. 5 In that work, both air 5,6 and water 6 convection cooling of a sheet of rubber removed from a mold at a target minimum state of cure were investigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of initial elastomer temperature on the transient temperature profiles and the resulting cure times for a molded component have been investigated previously [1]. Research has been reported concerning the temperature and state of cure profiles that occur within a component during cooling after demolding [2] and also for simulation of the state of cure profile in a tire during molding using variable thermal conductivity and time varying boundary conditions [3]. More comprehensive general information on heat transfer in the processing of rubber is available [4].…”
Section: Introductionmentioning
confidence: 99%